2018
DOI: 10.1177/1751143718774713
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of cardiac arrest in the intensive care unit: A systematic review and meta-analysis

Abstract: The incidence of cardiac arrest in the intensive care unit (ICU-CA) has not been widely reported. We undertook a systematic review and meta-analysis of studies reporting the incidence of cardiac arrest in adult, general intensive care units. The review was prospectively registered with PROSPERO (CRD42017079717). The search identified 7550 records, which included 20 relevant studies for qualitative analysis and 16 of these were included for quantitative analyses. The reported incidence of ICU-CA was 22.7 per 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 28 publications
5
25
3
Order By: Relevance
“…Due to clinically important differences, ICU-CA should be considered separately from IHCA in a general ward [14]. The incidence of ICU-CA varies greatly in the literature (4-78/1000 admissions) [14,15]. Survival rates to discharge after ICU-CA are diverse and range from 2 to 79%, mainly depending on the ICU population studied [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to clinically important differences, ICU-CA should be considered separately from IHCA in a general ward [14]. The incidence of ICU-CA varies greatly in the literature (4-78/1000 admissions) [14,15]. Survival rates to discharge after ICU-CA are diverse and range from 2 to 79%, mainly depending on the ICU population studied [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of ICU-CA varies greatly in the literature (4-78/1000 admissions) [14,15]. Survival rates to discharge after ICU-CA are diverse and range from 2 to 79%, mainly depending on the ICU population studied [14,15]. However, one recent study in critically ill patients with COVID-19 reported a mortality rate of 88% [11].…”
Section: Introductionmentioning
confidence: 99%
“…In-hospital pediatric cardiac arrest occurs in 2-6% of pediatric intensive care admissions (8)(9)(10). Despite the signi cant improvement in resuscitation science and practice over the last two decades (11), cardiac arrests had a signi cant impact on hospital resources and a signi cantly high mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate, consider the United Kingdom's in-hospital mortality rates, which are around 23% in ICU settings [3] and 4% in secondary wards [21]. Similarly, cardiac arrest incidence is estimated to be 2.3% of ICU admissions [2]. Nevertheless, most current adversity-prediction models are benchmarked using the Area Under the Curve (ROC-AUC) [1], [10], [29], [39], [60], which is known to overestimate model performance on minority outcomes under imbalanced distributions [17], [53].…”
Section: Introductionmentioning
confidence: 99%